Cinematic virtual reality: Towards the spatialized screenplay. (1st June 2018) - Ross, Miriam; Munt, Alex
This article considers how screenwriting might operate in the newly established medium of cinematic virtual reality (CVR). In Part One, we take a wide view of ways to consider screenwriting and development for CVR. Our approach theorizes CVR in the tradition of picture-making (or image-making) practices that can be traced within a broader history of the visual arts – from painting, to photography and contemporary art. In this way, we lay open the possibility for CVR to find diverse paths as it responds to narrative concerns rather than suggest it should merely repeat the consolidation of narrative that occurred with the transition of exploratory early cinema to the dominant Classical Hollywood system. In Part Two, our case study approach considers co-author, Miriam Ross', CVR practice-based research to allow a discussion of the format that can be used for delivery of the CVR screenplay. Our aims are to connect a historically based spatialization of the image with the question of the spatialization of the screenplay for CVR 360-degrees media. The agenda is to expand the conversation around CVR to reflect upon, and inspire, new ways of thinking (and seeing) the potential for the development of screen ideas in this medium.